Prevalence and Phylogenetic Diversity of Pathogenic Fusarium Species in Genotypes of Wheat Seeds in Three Rift Valley Regions, Kenya - Otieno P. Kheseli; Imbahale S. Susan; Okoth Sheila; Miriam Otipa; Wekesa V. Wafula (Advances in Agriculture)
Wheat is a source of nutrients for around 40% world’s population and the second most important cereal crop in Kenya. However, Fusarium head blight (FHB) hinders sustainable sufficient production of the crop, causing both economic and health losses. With the emerging unfavorable climatic changes, effective disease management strategies and adequate seed system are necessary to meet the deficiency. Current information on prevalence of the causative pathogens in varieties of wheat genotypes is a critical prerequisite to such strategies. This study aimed at determining the prevalence of pathogenic Fusarium species in seeds of developed varieties of wheat genotypes in three major wheat-producing regions in Kenya. A total of 260 samples of 18 wheat genotypes from 123 farms were collected. Peptone pentachloronitrobenze agar was used for fungal isolation, while identification of Fusarium spp. was based on the gene encoding translation elongation factor 1-α (tef1-alpha) sequence analysis. Fusarium spp. isolated include Fusarium poae, F. tricinctum, F. heterosporum, F. culmorum, F. equiseti, Fusarium sp., F. verticillioides, and F. oxysporum. There was no significant difference in prevalence of Fusarium spp. pathogens among the three regions studied. Fusarium spp. diversity index for Nakuru was 2.008, Narok was 1.4603, and Uasin Gishu was 1.2337. Wheat produce from farm-saved seeds yielded 66.25% of the isolates, while the produce from certified commercial wheat seeds yielded 33.75% of the isolates. The significant finding of the study is that Fusarium spp. associated with mycotoxins that contaminate the wheat food chain seem to be flourishing in all the sampled wheat seed genotypes from the regions studied. Information on the prevalence and diversity of the pathogens on persistence of the disease in the crop is critical in advancing integrative FHB control measures.